2015
DOI: 10.4315/0362-028x.jfp-14-491
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Curing Ingredients Derived from Purified and Natural Sources on Inhibition of Outgrowth during Cooling of Deli-Style Turkey Breast

Abstract: The antimicrobial impact of purified and natural sources of both nitrite and ascorbate were evaluated against Clostridium perfringens during the postthermal processing cooling period of deli-style turkey breast. The objective of phase I was to assess comparable concentrations of nitrite (0 or 100 ppm) and ascorbate (0 or 547 ppm) from both purified and natural sources. Phase II was conducted to investigate concentrations of nitrite (50, 75, or 100 ppm) from cultured celery juice powder and ascorbate (0, 250, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…In addition, results of this study validate that >50 ppm of nitrite plus I. 0% FE or CSV provided sufficient inhibition of C. perfringens to allow for safe chilling of deli-style turkey breast over 15 h, following the critical parameters outlined in FSIS Appendix B. Supplementing purified or natural nitrite with ascorbate, a cure accelerator from purified and natural (cherry powder) sources, has been demonstrated to be a viable option to inhibit growth of C. perfringens during extended chilling (16). Along with ascorbate, the results of this study provide additional options for meat processors to incorporate adjunct ingredients and safely chill alternative cured products.…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…In addition, results of this study validate that >50 ppm of nitrite plus I. 0% FE or CSV provided sufficient inhibition of C. perfringens to allow for safe chilling of deli-style turkey breast over 15 h, following the critical parameters outlined in FSIS Appendix B. Supplementing purified or natural nitrite with ascorbate, a cure accelerator from purified and natural (cherry powder) sources, has been demonstrated to be a viable option to inhibit growth of C. perfringens during extended chilling (16). Along with ascorbate, the results of this study provide additional options for meat processors to incorporate adjunct ingredients and safely chill alternative cured products.…”
Section: Resultssupporting
confidence: 58%
“…Conversely, the antimicrobial impact observed with the relatively low nitrite concentration included in this study can be increased with the addition of an antimicrobial. It is important to note that the treatments evaluated in this study did not contain ascorbate, which likely would have further enhanced the observed inhibition in treatments containing nitrite (16). Jackson et al (9) also reported variability between clean-label antimicrobial ingredients, based on their in hibitory effects against C. perfringens when used in formulations with natural sources of nitrite.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations